PESAN KEMENTERIAN AGAMA DALAM MODERASI MELALUI MEDIA SOSIAL INSTAGRAM - Wuri Arenggoasih; Corona Raisa Wijayanti (Fakultas Dakwah dan Komunikasi, 2020)
Certainly, everyone knows diversity in Indonesia but everyone does not necessarily understand and respect it. Even though according to the rule of law, Indonesia guarantees freedom of religion, diversity of ethnic groups, languages and cultures. But in reality, the SARA dispute still continues to this day. Regrettably, SARA disputes make quarrels not only in real life but also on social media. As the most social media user, the sensitivity of SARA issues must be a joint vigilance. This was realized by the Ministry of Religion by raising the theme